Efficacy of Impact Mixtures and Timings in Field Corn - Randall S. Currie; Patrick W. Geier (Kansas Agricultural Experiment Station Research Reports, 2023)
The objective of this research was to determine the utility of topramezone (Impact) herbicide for efficacy in corn. An experiment evaluated Impact with various tank mix and premix partners at several application timings for weed control in corn. Most herbicides provided excellent control of Palmer amaranth, common lambsquarters, and green foxtail. When Impact alone was applied late postemergence (LPOST) following Dual II Magnum (metolachlor) applied preemergence (PRE), kochia and Russian thistle control was less than 85%. Herbicides applied early postemergence (EPOST) or postemergence (POST) provided the best johnsongrass control early in the season, but no treatments controlled johnsongrass more than 90% late in the season.
Keywords: Sequential application; residual control; palmer amaranth; lambsquarters; foxtail